Documenting need for naloxone distribution in the Los Angeles County jail system. (May 2019) - Davidson, Peter J.; Wagner, Karla D.; Tokar, Paula L.; Scholar, Shoshanna
Abstract: Background: The Los Angeles County Jail system is the largest jail system in the United States, with an average daily inmate population of 17, 024 in 2017. Existing literature shows the weeks following release from incarceration are associated with increased risk of overdose death among individuals who previously used opioids. One response is to train inmates in overdose prevention and response (OPR) and to provide the opioid antagonist naloxone on release. However, in large jail systems training all inmates can be logistically and financially difficult, leading to interest identifying individuals most likely to benefit from such programs. Method: In 2017, the Los Angeles County Office of Diversion and Reentry collaborated with the Los Angeles County Sheriff Department to conduct an OPR needs assessment evaluation with all inmates entering the jail over a two week period. Results: 3781 inmates provided complete data for this analysis (3315 men, 466 women). 17% reported using opioids within the last 12 months, 7% reported witnessing an overdose within the last 12 months, and 5% report ever having received medication assisted treatment (MAT). 39% reported interest in being trained in overdose prevention and response. The single largest predictor of interest in OPR was being present at an overdose in the past year. Conclusion: Our results suggest OPR should be provided to all inmates who opt-in to receiving training regardless of other risk factors. Our results also suggest this population has had little prior exposure to MAT and incarceration could represent a significant opportunity to provide such evidence-based treatments. Highlights: Interest in receiving overdose prevention training is high among inmates entering jail. Witnessing an overdose in the past year is the largest predictor of such interest. Overdose prevention training should be offered to all inmates who opt-in.